1996
DOI: 10.1007/s003359900097
|View full text |Cite
|
Sign up to set email alerts
|

Production of congenic mouse strains carrying NOD-derived diabetogenic genetic intervals: An approach for the genetic dissection of complex traits

Abstract: Insulin-dependent (Type 1) diabetes (IDD) in the NOD mouse is inherited as a complex polygenic trait making the identification of susceptibility genes difficult. Currently none of the non-MHC IDD susceptibility genes in NOD have been identified. In this paper we describe the congenic mouse approach that we are using for the dissection of complex traits, such as IDD. We produced a series of six congenic strains carrying NOD-derived diabetogenic genomic intervals, which were previously identified by linkage anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
97
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 29 publications
(34 reference statements)
0
97
0
Order By: Relevance
“…To confirm the susceptibility loci and identify the responsible genes in animal models of type 1 diabetes, many congenic strains have been produced in NOD mice and BB rats. These studies have shown that most congenic strains carrying susceptibility allele(s) on nondiabetic genetic backgrounds do not develop diabetes (12)(13)(14). In addition, most congenic strains carrying resistant allele(s) on diabetes-prone genetic backgrounds suppressed the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm the susceptibility loci and identify the responsible genes in animal models of type 1 diabetes, many congenic strains have been produced in NOD mice and BB rats. These studies have shown that most congenic strains carrying susceptibility allele(s) on nondiabetic genetic backgrounds do not develop diabetes (12)(13)(14). In addition, most congenic strains carrying resistant allele(s) on diabetes-prone genetic backgrounds suppressed the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the susceptibility genes in type 1 diabetes, several studies on the genetic reconstitution of the disease on nondiabetic genetic backgrounds have been performed but have been unsuccessful to date (12)(13)(14). The congenic rat strain carrying two major susceptibility alleles, the RT1 u haplotype and Lyp/Ian4l1, of the BB rat on the F344 genetic background did not exhibit diabetes or insulitis (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we used NOD, C57BL/6, B6.G7 mice (C57BL/6-congenic mice with an introgressed NOD MHC interval; the B6.G7 mice do not develop diabetes, although they develop minor pancreatic lymphocytic infiltration; Ref. 47 …”
Section: N Onobese Diabetic (Nod)mentioning
confidence: 99%
“…At present, at least 20 genes are thought to play a role in this complex, multigenic process (1). The strongest genetic contribution is from the major histocompatibility complex (MHC) class II molecule, I-A g7 ; however, even two copies of I-A g7 are insufficient to mediate diabetes when placed on a nonautoimmune non-MHC background (3). Therefore, although substitution of other MHC class II molecules can prevent diabetes (indicating that I-A g7 is necessary for disease), it is not both necessary and sufficient; many non-MHC Idd loci contribute critically to the disease process.…”
mentioning
confidence: 99%